THE INFLUENCE OF BRANDING STRATEGY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY (Case Study on Customer Of Mister Geprek 3 in Bandar Lampung): PENGARUH STRATEGI BRANDING DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pada Kosumen Mister Geprek 3 Unila di Bandar Lampung) - Yana, Komang Niko; Sugiono, Arif; Saptiani, Winda (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the influence of branding strategy and customer satisfaction on customer loyalty in purchasing products at Mister Geprek 3 Unila in Bandar Lampung. The independent variables used in this study are Branding Strategy (X1), Customer Satisfaction (X2), and Customer Loyalty (X3). The type of this research is explanatory with a quantitative approach. The population in this study were customers of Mister Geprek 3 Unila. The data were obtained from a questionnaire using a Likert scale, which was distributed by Google Form to WhatsApp social media by the WhatsApp group and personal chat. The sample in this study amounted to 385 respondents who were taken using a purposive sampling technique. The data in this study were analyzed using multiple linear regression analysis with the SPSS 29.0 tool. The results of this study indicate that branding strategy and customer satisfaction simultaneously have a significant effect on customer loyalty at Mister Geprek 3 Unila in Bandar Lampung, with R Square value of 0.666, or 66.6%. While the parsially results show that branding strategy and customer satisfaction variables have a significant influence on customer loyalty, Mister Geprek 3 Unila in Bandar Lampung.